Glycolytic activity is required for the onset of neural plate folding during neural tube closure in mouse embryos - Sakai, Daisuke; Murakami, Yuki; Shigeta, Daichi; Tomosugi, Mitsuhiro; Sakata-Haga, Hiromi; Hatta, Toshihisa; Shoji, Hiroki (Frontiers in Cell and Developmental Biology, 2023)
Physiological hypoxia is critical for placental mammalian development. However, the underlying mechanisms by which hypoxia regulates embryonic development remain unclear.We discovered that the expression of glycolytic genes partially depends on hypoxia in neuroepithelial cells of E8.25 mouse embryos. Consistent with this finding, inhibiting glycolysis during the early phase of neural tube closure (E8.0-8.5) resulted in a neural tube closure defect. In contrast, inhibiting the electron transport chain did not affect neural tube formation. Furthermore, inhibiting glycolysis affected cell proliferation, but not differentiation and survival. Inhibiting glycolysis repressed the phosphorylation of myosin light chain 2, and consequent neural plate folding. Our findings revealed that anaerobic glycolysis regulates neuroepithelial cell proliferation and apical constriction during the early phase of neural tube closure.